Content Mastery Service Model to Improve Student Skills in Lessons Learned in Classical Formats Content Mastery Service Model to Improve Student Skills in Lessons Learned in Classical Formats - Nurfarida Deliani; Prayitno Prayitno; A Muri Yusuf; Jamaris Jamna (Jurnal Aplikasi IPTEK Indonesia, 2018)
Skills students ask a low asking in the learning process can disrupt the effective learning process at school. Questioning skills that students need to improve are the attitude about the material to be asked, how to ask for an opportunity to ask, the attitude when given the opportunity to ask, the attitude when the friend is given the opportunity to ask questions, the effort summarizes the whole question material. Based on this, the role of guidance and counseling is expected to meet the learning needs of students. One model that can be done to improve questioning skills is to provide content mastery services. Content mastery services help students, groups or classes to master a particular skill or competency consisting of 5 stages: the delivery, exploration, interpretation, coaching and assessment phases. With this content mastery service, it is hoped to improve the students' skills inquiring. The research method used to develop this model is R & D (Reseach and Development) by following the step of developing the model of ADDIE (Analyze, Design, Development, Implementation, Evaluation